What is Said and Indirect Speech Reports - Odrowąż-Sypniewska, Joanna (Research in Language, 2012)
In their Insensitive Semantics (2005) Cappelen and Lepore argue for the Controversial Aspect (CA) which is a part of their Speech Act Pluralism and which says that speakers don’t have privileged access to what they say. Gross (2006) criticizes C&L’s argument for CA and urges them to abandon that claim. I argue that on C&L’s broad understanding of the notion of what is said, CA (and whole SAP) is trivial, whereas on a more restricted understanding CA is indeed controversial and plausibly false. Moreover, the broad reading of what is said is incompatible with one of C&L’s tests for context-sensitivity.